KEPEMIMPINAN SUAMI DALAM PERSPEKTIF ISLAM: FUNGSI DALAM MEMPERKUKUHKAN INSTITUSI KELUARGA: Husband’s Leadership in Islamic Perspective: Role in Strengthening the Family Institution - Putung, Siti Halimah; Azahari, Raihanah (Jurnal Syariah, 2020)
Leadership in an institution or organization is very important in determining the success or failure of any institutions. The need to have good leadership is even more important in a family institution as it is the first institution in human’s life which affect all stages of life. However, good leadership today is no longer practised in many families which cause various problems to arise in a family. Marital problems such as alimony, nusyuz, disloyal, communication problem, no religious upbringing and more are closely related to the aspect of husband’ leadership in a family. Thus, this article discusses the husband’ leadership from the Islamic perspective as an important aspect which should be given attention and empowered to strengthen the family institution in this country. This research studied and analysed literature writings of Islamic scholars, especially the tafsīr, ḥadīth and fiqh scholars for clarification of husband’s leadership and its functions in a family institution. The study found that husband’s leadership has a wide meaning and it consists of three important functions namely protection, guidance and control. A good understanding on husband’s leadership and its function in a family institution will improve the understanding of integrity and persistence of a family as well as to prevent misunderstanding about the concept of leadership in a family.